ADDENDUM TO ‘A Study on the Eigenmodes Constructed in the Conductor Backed Coplanar Waveguide’ - Kim, Yeong Min (Transactions on Engineering and Computing Sciences, 2023)
In this study, finite element method has been carried out to calculate the eigenmode formed in the micro-script, conductor-backed slot line and conductor-backed coplanar waveguides. The eigenmodes have been represented with the electric field, 3D electric potential and electric equipotential contours. The electric potentials together with electric fields have improved understanding of eigenmodes of the waveguides. In particular, the electric potentials have been useful for revealing multiple and complex mixed peaks. In previous manuscript, the eigenmodes of the spectra have been mainly analyzed using electric fields. Comparing these results, it could be said that the interpretation based on the potential difference along with the electric field is more reliable. In other words, if the computational capacity of the personal computer is large enough to calculate the electric field and potential simultaneously, calculating these factors and analyzing the spectra based on them would result in a more reliable interpretation.